2009
DOI: 10.1002/jgm.1362
|View full text |Cite
|
Sign up to set email alerts
|

Combining angiogenic gene and stem cell therapies for myocardial infarction

Abstract: Co-injection of MLCVEGF and MSCs in ischemic hearts can result in better cardiac function and MSC survival, compared to their individual injections, as a result of the additive effects of each therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 42 publications
(46 reference statements)
5
43
1
1
Order By: Relevance
“…There are many studies on combining MSCs and VEGF gene therapy for protecting neurons against hypoxic ischemic injury ), promoting MSC proliferation (Crespo-Diaz et al 2011, enhancing the efficacy of MSCs in the swine model of myocardial infarction (Liu et al 2009) and promoting cardiac function and MSC survival (Pons et al 2009). Some studies have shown that MSCs could also achieve the biological effects by secreting VEGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies on combining MSCs and VEGF gene therapy for protecting neurons against hypoxic ischemic injury ), promoting MSC proliferation (Crespo-Diaz et al 2011, enhancing the efficacy of MSCs in the swine model of myocardial infarction (Liu et al 2009) and promoting cardiac function and MSC survival (Pons et al 2009). Some studies have shown that MSCs could also achieve the biological effects by secreting VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…The family of vascular endothelial growth factor (VEGF) molecules are potent initiators and regulators of angiogenesis with VEGF 165 being the most powerful and widely distributed within the body for promoting angiogenesis (Neufeld et al 1999;Zhao et al 2007). BMMSCs transfected with the VEGF gene have been used in the treatment of cardiovascular disease (Liu et al 2009;Pons et al 2009;Zisa et al 2009), bone regeneration , neurodegenerative , and Achilles tendon repair (Hou et al 2009). However, there has not been research on VEGF gene modified BMMSCs and its role in the liver disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines secreted by solid tumours have been shown to exert a positive chemotactic effect on mesenchymal stem cells. Thanks to that, these cells might be used as vectors transporting cytotoxic agents (granzymes, perforin, granulysin, cathepsins, TIA-1) that induce apoptosis in tumour cells and locally release high levels of cytokines that stimulate stronger immune responses [48,49]. This property of mesenchymal stem cells also allows attempts to modify the cell genome in order to enhance the cellular expression of interferon γ, IL-12, and many other substances that accelerate cancer cell destruction.…”
Section: Novel Cancer Stem Cell-targeting Therapymentioning
confidence: 99%
“…Therefore, the mechanisms leading to stem/progenitor cell dysfunction need to be better characterized and will provide interesting novel approaches to optimize cellbased treatment approaches. Moreover, strategies to improve cardiac homing and engraftment of stem/progenitor cells may optimize the effect the results of this treatment approach (Pons et al 2008;Pons et al 2009;Tang et al 2009;Zhao et al 2009).…”
Section: Future Directions Of Cell Based-therapy For Ischemic Heart Dmentioning
confidence: 99%